Endothelial function is impaired in relation to alcohol intake even in the case of light alcohol consumption in Asian men; Flow-mediated Dilation Japan (FMD-J) Study. (1st March 2017) - Oda, Nozomu; Kajikawa, Masato; Maruhashi, Tatsuya; Iwamoto, Yumiko; Kishimoto, Shinji; Matsui, Shogo; Hidaka, Takayuki; Kihara, Yasuki; Chayama, Kazuaki; Goto, Chikara; Aibara, Yoshiki; Nakashima, Ayumu; et al.
Abstract: Background: Heavy drinking should be a predictor of endothelial dysfunction. However, there is little information on the effects of light to moderate alcohol consumption on endothelial function. The purpose of this study was to estimate the effects of dose-dependent alcohol consumption on endothelial function. Methods: We measured flow-mediated vasodilation (FMD) in 2734 men aged 21–81 years who provided information on alcohol intake at 3 general hospitals. The subjects were divided into 5 groups; non-drinkers (0 g/week), light drinkers (> 0 to 140 g/week), moderate drinkers (> 140 to 280 g/week), heavy drinkers (> 280 to 420 g/week), and excessive heavy drinkers (> 420 g/week). Results: FMD showed a gradual decrease in accordance with alcohol consumption in the entire study population (non-drinkers, 6.6 ± 3.4%; light drinkers, 6.2 ± 3.0%; moderate drinkers, 6.0 ± 3.0%; heavy drinkers, 5.5 ± 2.9%; excessive heavy drinkers, 5.3 ± 3.0%; P  < 0.001). There was a significant difference in FMD between the light alcohol drinker group and the non-drinker group ( P  = 0.015). After adjustment for other risk factors, the odds of having FMD in the lowest quartile was found to be significantly increased in the 4 drinker groups than in the non-drinker group: light (OR, 1.38; 95% CI, 1.10 to 1.75), moderate (OR, 1.36; 95% CI, 1.01 to 1.82), heavy (OR, 2.05; 95% CI, 1.46 to 2.87), excessive (OR, 2.04; 95% CI, 1.43 to 2.89). Conclusion: These findings suggest that FMD is impaired in relation to alcohol consumption and that FMD is significantly smaller even in light alcohol drinkers than in non-drinkers. Alcohol intake per se may be harmful for vascular function. Highlights: There is little information on the effects of alcohol intake on endothelial function. Endothelial function was impaired in the light alcohol intake group than in the non-drinker group. Alcohol intake per se may be harmful for vascular function.